High-resolution tomographic volumetric additive manufacturing - Damien Loterie (Nature Portfolio, 2020)
Tomographic additive manufacturing produces complex parts with a wide range of printable materials but remains limited in terms of resolution. Here, the authors tune the étendue of the light source and accurately control the photopolymerization kinetics using an integrated feedback system, leading to the fabrication of high resolution features.